Las letras del cancionero nacional como estrategia metodológica para la enseñanza de la poesía, en la asignatura de lengua y literatura, en los estudiantes del segundo de bachillerato del Colegio de Bachillerato U.N.E. de la ciudad de Machala, periodo lectivo 2014 – 2015 - Gallegos Gaona, Pedro Hernán (2014)
Every art form has a language, a vehicle through which man conveys ideas and feelings. Our music identifies us with their cultural expression sand linguistic content, where different musical genres that represent the ethnic and cultural diversity of Ecuador. The national music consists urbanized versions of a set of musical genre indigenous and mestizo representing musical as esthetics of elites. In the group of indigenous music are some ritual dances as associated with agricultural festivals of the Indian calendar, as Yaraví, the dancing, the Yumbo and San Juanito. In the group of mestizo music are the hall, the parade, the albazo and typical air, which combine melodies and rhythms of native and European origin. Of these genera, the hall is considered the musical symbol of the country; to the extent that the term shall way and country music are used interchangeably as synonyms of Ecuadorian music. Therefore, in this research we propose in order to "Identify what forms of implementation of the national song lyrics as a methodological strategy pear teaching poetry in the subject of language and literature, students of second year of “UNE High School” in the city of Machala. To gather information was done using the following techniques: the interview, survey and direct observation to students and teachers of the subject of Language and Literature. For a description of the information we use inductive and deductive methods as well as the synthetic method. Moreover, the hypothesis, variables and indicators, which help research verifying you are you break. In response to the need of students, teachers and educational institution, we propose an alternative proposal which describes interactive activities using as a methodological strategy to develop national songs poetic creation.